2021
DOI: 10.4239/wjd.v12.i9.1518
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors affecting the etiology and management of type 1 diabetes mellitus: A narrative review

Abstract: Type 1 diabetes (T1D) is one of the most common chronic diseases in children and adolescents worldwide. Its etiopathogenesis results from the interplay of genetic and environmental variables. Among the latter, psychological stress has been implicated in disease onset as well as disease management. Various studies, including large population-based studies, have highlighted the role of stressful life events in the etiopathogenesis of T1D. In this article, we also emphasize the importance of attachment in the ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Some studies confirmed that elevated diabetes-related distress was experienced by 20–30% of people with T1DM, suggesting a widespread clinical problem in this population as well 5 . Unlike type 2, the onset of T1DM is linked to a younger age and is often associated with stressful life events; psychosocial factors were shown to play a role in both its etiopathogenesis and disease management 6 . Diabetes-related distress in adults with T1DM is associated with suboptimal glycemic control and tends to be higher for women and relatively younger adults 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies confirmed that elevated diabetes-related distress was experienced by 20–30% of people with T1DM, suggesting a widespread clinical problem in this population as well 5 . Unlike type 2, the onset of T1DM is linked to a younger age and is often associated with stressful life events; psychosocial factors were shown to play a role in both its etiopathogenesis and disease management 6 . Diabetes-related distress in adults with T1DM is associated with suboptimal glycemic control and tends to be higher for women and relatively younger adults 2 .…”
Section: Introductionmentioning
confidence: 99%
“…22 These findings add to a growing body of literature demonstrating the importance of psychosocial factors—both at the individual/family and community/society levels—in self-management and diabetes-related health outcomes for individuals with T1D. 23 This study advances this line of current literature by examining such factors within the standard of clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the interplay between T1D and psychiatric disorders on brain functions may be another explanation. Having psychiatric disorders may considerably impair one's diabetes management, 43,44 resulting in poor glycemic control, elevated risks of hypoglycemia and ketoacidosis, and frequent diabetes-related hospitalizations. Evidence showed that chronic hyperglycemia, acute hypoglycemia, and ketoacidosis could affect central nervous system development, 45 causing neurocognitive dysfunctions, such as in attention, working memory, and psychomotor functions.…”
Section: Discussionmentioning
confidence: 99%